THU0378 COEXISTENCE OF ANKYLOSING SPONDYLITIS AND RHEUMATOID ARTHRITIS (ANALYSIS OF 73 CASES). (June 2019) - Robles, Bryan-Josué Flores; Pinillos, Valvanera; Elena-Ibáñez, Angel; Labrador-Sánchez, Eztizen; Merino-Meléndez, Leticia; López-Martín, Juan Antonio; Ramalle-Gómara, Enrique
Abstract : Background: The coexistence of rheumatoid arthritis (RA) and ankylosing spondylitis (AS) in the same patient is a rarely described phenomenon. Both ankylosing spondylitis and rheumatoid arthritis are common entities in the field of rheumatic diseases with a high impact on the patient's quality of life and morbidity and mortality. The possibility of the coexistence of both diseases in the same person is not known exactly, however, with the data published to date, it is estimated that it ranges from 1 in 500, 000 to 1 in 2, 000, 000. Objectives: The epidemiological, clinical and study characteristics (radiographic/laboratory) of 73 patients with concomitant diagnosis of RA and AS are described. It includes 71 patients detected in the literature (32 articles) and 2 own cases Methods: The platforms used for the search using the terms AR and AS (coexistence/concomitance/concurrence) were Pubmed, Medline, Embase, Scopus, hospital virtual libraries, non-indexed journals and a secondary manual search. All the articles were taken into account, regardless of the language in which they were written, making the relevant translations (1 article in French, 1 article in Portuguese, 1 article in Spanish and the rest in English), and only those well documented cases were included. Results: Of the total of registered cases, 55 patients were men (75.3%), with a mean age of 54 years, and a mean age of onset of the disease at 33.7 years (SD 14.0). Ankylosing spondylitis was the first of the two diseases diagnosed in 52.2% of cases (35/67). The mean duration of the disease (RA or AS) up to the time of diagnosis of both was 19 years. The first symptom of onset was low back pain in 50% of cases (34/68), followed by arthritis in 46% of cases (32/68), 56% of patients (36/64) had nodules rheumatoid and 85% of patients had presented low back pain at some point of their assessment. In 15% of the patients (11/73) the presence of uveitis was documented (in some old articles the term of iritis was limited), in 22% of cases there was extra-articular involvement (16/73), being the most frequent was the presence of Felty syndrome with 4 cases. (table 1 ) Regarding the findings in the imaging studies, up to 78% of the patients had syndesmophytes in the spine (either in plain radiography). 88% (62/70) presented erosions in the X-rays of the hands and/or feet, the Radiological sacroiliitis was present in almost all patients 72/73, RF was positive in 90%, in 9 of the 11 patients in whom anti-CCP was performed were positive, and, in addition, almost 90% of the cases were HLA B-27 positive Conclusion: The coexistence of AR and SpA is highly uncommon. With the data obtained, there seems to be a greater aggressiveness in the evolution, since most of them present an erosive radiological pattern, positivity for RF, involvement of the axial skeleton and presence of rheumatoid nodules in a frequency higher than that which occurs in patients with diagnosis isolated from either of the two entities. Reference: [1] Simon TA, Kawabata H, RayN, Baheti A, Suissa S, Esadile JM. Prevalence of co-existing autoinmune disease in rheumatoid arthritis: A cross-sectional study. Adv Ther 2017; 34: 2481-2490.E Abbreviations: DT= Typical deviation Disclosure of Interests: Bryan-Josué Flores Robles Grant/research support from: Transport and hotel, Valvanera Pinillos: None declared, Angel Elena-Ibáñez: None declared, Eztizen Labrador-Sánchez: None declared, Leticia Merino-Meléndez: None declared, Juan Antonio López-Martín: None declared, Enrique Ramalle-Gómara: None declared